Survivin S81A Enhanced TRAIL's Activity in Inducing Apoptosis - Ferry Sandra; Roya Khosravi-Far (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Survivin is rarely expressed in normal healthy adult tissues, however, it is upregulated in the majority of cancers. Survivin, which belongs to IAPs family, has been widely reported to protect cells from apoptosis by inhibiting caspases pathway. Survivin’s mitotic activity is modulated by many kinases, and its phosphor status can also influence its ability to inhibit apoptosis. There are several important survivin’s phosphorylation sites, such as S20 and T34. We have continued our investigation on other potential survivin’s phosphorylation sites that could be important site for regulating survivin’s cyto-protection.METHODS: By assuming that S81 could be a potential target to modify activity of survivin, wild-type survivin (Survivin), antisense survivin (Survivin-AS), mutated-survivin Thr34Ala (Survivin-T34A) and mutated-survivin Ser81Ala (Survivin-S81A) were constructed and inserted into pMSCV-IRES-GFP vector with cytomegalovirus (CMV) promoter. Each retroviral product was produced in BOSC23 cells. LY294002 pretreatment and TRAIL treatment along with infection of retroviral products were performed in murine fibrosarcoma L929 cells. For analysis, flow cytometric apoptosis assay and western blot were performed.RESULTS: In our present study, survivin for providing cytoprotection was regulated by PI3K. The results showed that LY294002, an inhibitor of PI3K, effectively suppressed survivin-modulated cytoprotection in a TRAIL-induced apoptotic model. In addition, mutated survivin S81A showed marked suppression on survivin’s cytoprotection. Along with that, TRAIL’s apoptotic activity was enhanced for inducing apoptosis.CONCLUSION: We suggested that survivin could inhibit apoptosis through PI3K and S81A could be another potential target in order to inhibit Survivin-modulated cytoprotection as well as to sensitize efficacy of TRAIL or other related apoptotic inducers.KEYWORDS: apoptosis, survivin, TRAIL, S81A, L929, LY294002